Assessing the effects of heavy metals and polycyclic aromatic hydrocarbons on benthic foraminifera: The case of Houshui and Yangpu Bays, Hainan Island, China - Zhang, Muhui; Yang, Chupeng; Cai, Guanqiang; Li, Shun; Nie, Xin; Zhou, Shuqin (Frontiers in Marine Science, 2023)
This work aimed to investigate the distribution of benthic foraminiferal assemblages in Houshui and Yangpu Bays, Hainan Island, and assess the relative effects of heavy metals, total organic carbon (TOC), and polycyclic aromatic hydrocarbons (PAHs) on foraminiferal assemblages. A total of 30 sites were sampled and analyzed for benthic foraminiferal assemblages, heavy metals, TOC, and PAHs. The organic matter in the study was derived primarily from algae according to the C/N ratios, and PAHs were generated by petroleum and combustion of petroleum products, as inferred from the diagnostic ratios of PAH isomers. Two-way hierarchical cluster analysis was used to classify the 35 common species into two species groups, and the 30 sites were classified based on their geographical location. CCA was used to investigate the effects of pollution on foraminiferal assemblages. The results showed that the effects of pollution on foraminiferal assemblages were in the order of heavy metals > TOC > PAHs. Furthermore, the species group I, which consisted of agglutinated taxa including Bigenerina nodosaria, Ammobaculites agglutinans, Textularia spp., T. foliacea, Haplophragmoides canariensis, and several tolerant species of hyaline forms, including Ammonia beccarii, Elphidium advenum, E. hispidulum, Quinqueloculina laevigata, and Q. seminula, was found to be positively influenced by heavy metals. In contrast, species group II, primarily composed of porcelaneous taxa such as Massilina laevigata, Spiroloculina communis, and some hyaline taxa including E. crispum and Elphidium spp., was found to be positively influenced by TOC and PAHs. This work suggest that heavy metal pollution is the main factor influencing foraminiferal assemblages in the study area. The observed positive effect of heavy metals on species group I may indicate the presence of metal-tolerant taxa, whereas the positive effect of TOC and PAHs on species group II suggests that these taxa may be more tolerant of organic pollution. The study highlights the potential of specific foraminiferal assemblages as bioindicators for assessing the impact of different types of pollution on marine ecosystems.